2021
DOI: 10.1101/gad.348797.121
|View full text |Cite
|
Sign up to set email alerts
|

Neural stem/precursor cells dynamically change their epigenetic landscape to differentially respond to BMP signaling for fate switching during brain development

Abstract: During neocortical development, tight regulation of neurogenesis-to-astrogenesis switching of neural precursor cells (NPCs) is critical to generate a balanced number of each neural cell type for proper brain functions. Accumulating evidence indicates that a complex array of epigenetic modifications and the availability of extracellular factors control the timing of neuronal and astrocytic differentiation. However, our understanding of NPC fate regulation is still far from complete. Bone morphogenetic proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 63 publications
0
12
1
Order By: Relevance
“…5E). A recent study reported that BMP2-induced genes are mostly enriched for neuronal and astrocyte differentiation (Katada et al, 2021), while our analysis did not identify these categories. The discrepancy may derive from difference in NSC culture, as ours was from E13 instead of E11 and E14, or different profiling methods, H3K4me3 versus RNA-seq.…”
Section: Genomic Relocation Of Smad4/psmad De-represses Cell Prolifer...contrasting
confidence: 89%
“…5E). A recent study reported that BMP2-induced genes are mostly enriched for neuronal and astrocyte differentiation (Katada et al, 2021), while our analysis did not identify these categories. The discrepancy may derive from difference in NSC culture, as ours was from E13 instead of E11 and E14, or different profiling methods, H3K4me3 versus RNA-seq.…”
Section: Genomic Relocation Of Smad4/psmad De-represses Cell Prolifer...contrasting
confidence: 89%
“…To test its use in prenatal NSC populations, neural stem cells dissected from the developing dorsal V-SVZ at embryonic day 15.5 were exposed to BMP4 with simultaneous withdrawal of EGF but maintenance of basic fibroblast growth factor (bFGF-2), and markers of cell proliferation and quiescence were quantified using fluorescence microscopy and flow cytometry. After 24 hours in media containing BMP4 and bFGF-2, levels of the proliferation marker Ki67 had significantly decreased compared to cells grown in control media containing bFGF-2 and epidermal growth factor (EGF) ( BMP4 has also been shown to direct NSCs into neuronal or astrocytic lineages depending on the time of expression (Katada et al, 2021); these effects that are directly antagonized and suppressed by EGF and FGF-2 to maintain stemness and self-renewal capacities (Lillien & Raphael, 2000;Sun et al, 2011). To ensure that the removal of EGF and exposure to BMP4 did not differentiation as reported for media containing only BMP4 without FGF-2, levels of Sox2, a transcription factor expressed by neural stem and progenitor cells, but not transit amplifying cells, were measured following acute (72 hours, Fig p-4EBP1/2 signaling decreases in embryonic NSCs following quiescence induction.…”
Section: Resultsmentioning
confidence: 99%
“…BMP4 has also been shown to direct NSCs into neuronal or astrocytic lineages depending on the time of expression (Katada et al, 2021); these effects that are directly antagonized and suppressed by EGF and FGF-2 to maintain stemness and self-renewal capacities (Lillien & Raphael, 2000; Sun et al, 2011). To ensure that the removal of EGF and exposure to BMP4 did not differentiation as reported for media containing only BMP4 without FGF-2, levels of Sox2, a transcription factor expressed by neural stem and progenitor cells, but not transit amplifying cells, were measured following acute (72 hours, Fig 2E) and prolonged (6 days, Fig 2F) exposure to BMP4.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the BMP signaling pathway plays different, sometimes even opposite, roles in different periods of neural differentiation [33]. The inhibition of BMP signaling is required during neural induction [34], while it plays a positive regulatory role in the formation of neural precursor cells [35]. As shown in Fig.…”
Section: The Effect Of Oh-gqds On the Histone Modi Cation-activated B...mentioning
confidence: 99%